Effect of hybrid nanofluids mixture ratio on the performance of a photovoltaic thermal collector. (23rd June 2020) - Wole‐Osho, Ifeoluwa; Adun, Humphrey; Adedeji, Michael; Okonkwo, Eric C.; Kavaz, Doga; Dagbasi, Mustafa
Summary: Solar photovoltaic‐thermal (PV/T) collectors, are hybrid collectors used to convert solar radiation into usable thermal and electrical energy. Recently, the field of research on PV/T is has focused on improving the efficiency of the PV/T collector by replacing the conventional heat transfer fluids (HTFs) with nanofluids. This article investigates the effect of hybrid nanofluids mixture ratio on the useful energy and overall efficiency of a PV/T collector operating with Al2 O3 ‐ZnO water nanofluid as the HTF. Experiments to measure the thermophysical properties of the hybrid nanofluids were conducted for various temperatures, volume concentrations, and mixture ratios, furthermore, accurate correlation models were proposed. Metrological data and energy output readings collected from the PV solar farm at Cyprus International University were used to validate our model. The study observed that at the optimum mixture ratio (0.47 of Al2 O3 in the hybrid), the electrical, thermal, and exergy efficiencies of the PV/T collector are 13.8%, 55.9%, and 15.13% respectively. Also, the cell temperature drops by 21% when the mass flow rate is 0.1 kg/s as compared to when it is 0.01 kg/s. Finally, the study concludes that by using the Al2 O3 ‐ZnO hybrid nanofluid an overall peak thermal efficiency of 91% can be attained, and this represents a 34% enhancement in the collector's performance when compared to water. Abstract : This research presents the first investigation into the effects of a hybrid nanofluid mixture ratio on the thermal and electrical performance of the PV/T system. This investigation is important because by understanding this behavior, the overall efficiency of the PV/T system can be improved without increasing the volume concentration of the hybrid nanofluid. Therefore allowing for some savings in material costs.